2016
DOI: 10.1038/srep27757
|View full text |Cite
|
Sign up to set email alerts
|

Transient ECM protease activity promotes synaptic plasticity

Abstract: Activity-dependent proteolysis at a synapse has been recognized as a pivotal factor in controlling dynamic changes in dendritic spine shape and function; however, excessive proteolytic activity is detrimental to the cells. The exact mechanism of control of these seemingly contradictory outcomes of protease activity remains unknown. Here, we reveal that dendritic spine maturation is strictly controlled by the proteolytic activity, and its inhibition by the endogenous inhibitor (Tissue inhibitor of matrix metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 57 publications
2
75
0
Order By: Relevance
“…1). In rats, transient proteolytic activity in the synaptomatrix accompanies long-term potentiation and dendrite maturation (Magnowska et al, 2016), which corroborates our model that Timp dynamically restricts synaptic modulation through localized ECM proteolysis. Crucially, pharmacologically balancing Mmp activity in timp null mutants with minocycline treatment restores BMP trans-synaptic signaling (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…1). In rats, transient proteolytic activity in the synaptomatrix accompanies long-term potentiation and dendrite maturation (Magnowska et al, 2016), which corroborates our model that Timp dynamically restricts synaptic modulation through localized ECM proteolysis. Crucially, pharmacologically balancing Mmp activity in timp null mutants with minocycline treatment restores BMP trans-synaptic signaling (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The functional importance of 5-HT7R/MMP-9-mediated processing of CD44 was further supported by the fact that treatment of hippocampal slices with 5-CT resulted in MMP-9-dependent accumulation of 55-kDa cleavage products of CD44, which was accompanied by impaired LTP impairment in the Schaffer collateral synapses (Figure 7). Previous studies revealed that MMP-9 inhibitors impair the late phase of CA1 LTP but have no effects 60 min after induction of LTP (Nagy et al, 2006), whereas this phase of LTP is impaired in MMP-9-overexpressing rats (Magnowska et al, 2016). In line with these data, MMP-9 inhibitor I did not affect CA1 LTP 60 min after induction of LTP but rescued the defect in LTP induced by 5-CT (Figure 7), supporting the view that stimulation of the 5-HT7R activates MMP-9 and that hyperactivity of MMP-9 impairs LTP.…”
Section: Discussionmentioning
confidence: 98%
“…Images of dendrites in different brain regions were acquired under 561 nm fluorescent illumination using a confocal microscope (63 objective, 1.4 NA) at a pixel resolution of 1024 × 1024 with a 3.43 zoom, resulting in a 0.07µm pixel size [24].…”
Section: Imagingmentioning
confidence: 99%
“…Refer [24,25] Refer [24,26] Refer [27,28,29,30] Aparatus Figure 1(c) with color transition from red to green describing the spine membership and dendrite membership value of a pixels(above). The block interactive module show the intensity thresholds ths(40) and th d (240) for the spine and dendrite respectively and the graph shows fuzzy membership curve for both spine(red) and dendrite(green).…”
Section: Procedures Referencesmentioning
confidence: 99%